Lyophilised protein formulations as a patient-centric dosage form: A contribution toward sustainability paradigm - Žiberna Maja Bjelošević; Grabnar Pegi Ahlin; Gašperlin Mirjana; Matjaž Mirjam Gosenca (Acta Pharmaceutica)
At present, society has embraced the fact apropos population aging and climate changes, that demand, amongst others, innovative pharmaceutical technologies, emphasising the development of patient-specific delivery systems and thus the provision of efficient and sustainable drugs. Protein drugs for subcutaneous administration, by allowing less frequent application, represent one of the most important parts of the pharmaceutical field, but their development is inevitably faced with obstacles in providing protein stability and suitable formulation viscosity. To gain further knowledge and fill the gaps in the already constructed data platform for the development of monoclonal antibody formulations, we designed a study that examines small model proteins, i.e., bovine serum albumin. The main aim of the presented work is to evaluate the effect of protein concentrations on critical quality attributes of both, pre-lyophilised liquid formulations, and lyophilised products. Through the study, the hypothesis that increasing protein concentration leads to higher viscosity and higher reconstitution time without affecting the stability of the protein was confirmed. The most important finding is that sucrose plays a key role in the lyophilisation of investigated protein, nevertheless, it can be predicted that, to ensure the beneficial effect of mannitol, its amount has to prevail over the amount of sucrose.